Xanthogranulomatous epithelial tumors/keratin-positive giant cell–rich tumors involving the head and neck: report of seven cases and review of the literature - Whaley, Rumeal D.; Agaimy, Abbas; Bridge, Julia A.; Stöhr, Robert; Din, Nasir Ud; Gagan, Jeffrey; Rampisela, Debby; Folpe, Andrew L.; Bishop, Justin A. (Virchows Archiv, 2024)
Xanthogranulomatous epithelial tumor (XGET) and HMGA2::NCOR2 fusion keratin-positive giant cell–rich tumor (KPGCT) are recently described morphologically overlapping rare neoplastic entities characterized by HMGA2::NCOR2 fusions, low-grade biological behavior, and a strong predilection for young females. To date, 47 cases have been reported with only four occurring in head and neck anatomic locations. In this study, we describe the clinicopathologic, immunohistochemical, and molecular findings of seven XGET/KPGCTs occurring in the head and neck region. The patients were six females and one male, aged 3.5–59 years old (median, 25 years). The tumors involved the ear, vocal cord, skull, neck soft tissue, and sinonasal cavity. Tumor sizes ranged from 1.5 to 6.7 cm. Histologically, the tumors were characterized by xanthogranulomatous histiocytes, osteoclast-like giant cells, and keratin-positive epithelioid cells. The XGET/KPGCTs involving the ear was remarkable for more cytologic atypia than previously described. Four cases had the HMGA2::NCOR2 fusion identified by NGS and three had HMGA2 gene locus alterations by FISH. Follow-up information was available for 3 of 7 patients (range 6–46 months). The patient with a vocal cord XGET/KPGCTs developed a local recurrence treated with excision. This study illustrates that XGET/KPGCTs involves the head and neck region as well, where it may be unexpected and hence under-recognized, and expands the anatomic locations of involvement to include unreported sites (ear, vocal cord, and sinonasal tract).
CRIS-Team Scopus Importer:2024-08-30
Keywords: HMGA2::NCOR2; Keratin-positive giant cell–rich tumor; KPGCT; Xanthogranulomatous epithelial tumor; XGET